ANALYSIS OF THE MAIN ECONOMIC INDICATORS AND TRENDS OF ORGANIZATION OF PASSENGER TRANSPORT IN UZBEKISTAN - Sevara Aytieva Allaberdievna (Modern American Journals, 2025)
The use of modern technologies in the effective organization and management of flows in the global supply chain is of particular importance in ensuring the timely provision of consumers' needs for finished products and raw materials . In this regard, in developed foreign countries, in particular, the USA, the Netherlands, Turkey, Russia, Germany, France, China, South Korea, Japan, special attention is paid to the development of new scientific and technical solutions for delivering cargo to consumers in the right volume, on time, to the right place, with high quality and at reasonable prices. Increasing transportation volumes, ensuring timely and guaranteed satisfaction of consumers' needs for cargo flows and ensuring economic efficiency are the most urgent tasks today.